美国小企业成长环境分析及对中国的启示 = An analysis on the growth environment of American small business : implications on China's small-medium enterprises - 缈晓星 Miao, Xiaoxing (2008)
This dissertation analyzes the development of small and medium enterprises (SME) and economic conditions for their development in U.S.A.